Visualization of Incisive Foramen in Intraoral Periapical Radiographs- A Comparative Radiographic Study - Niroula, Deepa; Poudel, Kalpana; Dahal, Sirjana; KC, Krishna (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Incisive foramen, a normal anatomical landmark in the anterior maxilla, appears as a radiolucency between the apices of the maxillary central incisors on intraoral periapical radiographs. This study was conducted to compare the visibility of the incisive foramen in between bisecting-angle and paralleling techniques.Methods: An analytical cross-sectional study was conducted among 100 patients selected by consecutive sampling method. Group 1 included patients with 50 radiographs obtained for visualization of incisive foramen using bisecting angle technique and Group 2 included 50 patients with radiographs using paralleling technique. Data was entered into Microsoft Excel Sheet and analyzed in SPSS version 24. Chi square/fisher’s exact test was done to determine the proportional difference between visualization of incisive foramen by using two techniques. The significance level was set at P